Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2020)

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Cost-effectiveness with equity: Raising learning for marginalised girls through Camfed's programme in Tanzania - Sabates, Ricardo; Rose, Pauline; Delprato, Marcos; Alcott, Benjamin (Policy Paper No. 18/2 (REAL Centre, University of Cambridge, 2018), 2018)
This policy paper provides a cost-effectiveness analysis of Camfed’s programme in Tanzania. Camfed’s programme adopts a multidimensional approach that is aimed at reaching marginalised girls at risk of dropping out from secondary schools by using interventions that are aimed at both increasing their chances of staying in school and learning.
Keywords: ___working_potential_duplicate; _not_EdTechHub